COMPARATIVE INVESTIGATION OF ROBBERY BY MEANS OF INTIMIDATION AND VIOLENCE FROM THE POINT OF VIEW OF THE LEGISLATOR IN THE PENAL CODE OF THE REPUBLIC OF AZERBAIJAN AND THE ISLAMIC REPUBLIC OF IRAN - Mohammad Yosefi , Caber Goliyv , Siyamak Shaker Sultan Ahmadi , Mortaza Shariati (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Based on the Islamic Penal Law, robbery can be described as one of the following categories according to some relevant conditions while its punishment can change to varying degrees: First, a robbery is considered "Hadd" (requiring graver punishment); in this case, the robber is sentenced to Hadd for the act of robbery. Second, a robbery committed via armed robbery or banditry, causing public horror, in which case it is regarded as Moharebeh and Corruption on Earth with its perpetrator being condemned as Mohareb and Worker of Corruption on Earth. Third, a robbery not involving any of the above conditions, in which case, it is known as Ta'zir (requiring canonical punishment; less serious than Hadd) with the robber facing less severe punishment. On the other hand, as per the Penal Code of the Republic of Azerbaijan, the acceptance of the element of seizure as the main element of robbery makes it difficult to accurately distinguish this offense from such offenses as fraud, vandalism, and even interference with the stolen property; as in each of these cases, the offender usually takes possession of the latter's property by considering proprietary interests to himself. To eliminate this problem, the courts in the Republic of Azerbaijan have sought on several occasions to provide criteria for the distinction of these financial offenses, as the basis of their decisions has sometimes been criticized by some lawmakers. This study pertains to a field of criminal law, as it sought to provide a comparative study of robbery using intimidation and violence in the view of the legislator in the Penal Code of the Republic of Azerbaijan and the Islamic Republic of Iran.